2006
DOI: 10.1300/j083v47n01_08
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Emotional Strain Among Spouse and Adult Child Caregivers

Abstract: This study used data from the 1999 National Long Term Care Survey to examine predictors of emotional strain between spouse and adult child caregivers using the frameworks of role theory and the stress process model. Secondary data analysis examined if and how emotional strain differed between the groups and what the predictors of emotional strain were for each group. Common group predictors of emotional strain were elder's disruptive behaviors, caregiver's perceived overload, family disagreement, limitations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 30 publications
3
44
1
2
Order By: Relevance
“…This is consistent with Kang's (2006) more recent finding that adult children and spouses do not differ significantly in the amount of emotional strain reported. However, Kang (2006) also reported that this may indicate that adult child caregivers are able to cope with the caregiver experience better than spousal caregivers.…”
Section: Adult Child and Spousal Caregiverssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with Kang's (2006) more recent finding that adult children and spouses do not differ significantly in the amount of emotional strain reported. However, Kang (2006) also reported that this may indicate that adult child caregivers are able to cope with the caregiver experience better than spousal caregivers.…”
Section: Adult Child and Spousal Caregiverssupporting
confidence: 92%
“…In addition, the background of the caregiver (i.e., ethnicity, gender, or relationship to the care receiver) can influence the caregiver's experience. For example, it has been found that Caucasians reported higher levels of stress than African Americans (Hilgeman et al, 2009), women are more likely to report higher levels of stress than men (Koerner & Kenyon, 2007), and spouses are more likely to report higher levels of stress than adult children when it comes to caregiving (Kang, 2006).…”
mentioning
confidence: 99%
“…Two were carried out in the US, 135,136 two in Japan 137,138 and three in Europe. [139][140][141] Two 136,141 compared two different models of respite care.…”
Section: Update Of Systematic Review For Period December 2005-april 2008mentioning
confidence: 99%
“…Three studies 135,137,138 took an observational approach to look at predictors of carer outcomes, with use of service being one of the predictors. Both Japanese studies 137,138 were of this design and also the study by Kang 135 carried out in the US.…”
Section: Update Of Systematic Review For Period December 2005-april 2008mentioning
confidence: 99%
See 1 more Smart Citation